Ambivalensi Energi Terbarukan : Kendaraan Listrik Untuk Penurunan Emisi Karbon dan Dampaknya Terhadap Kerusakan Lingkungan di Indonesia - Muliana Mursalin , Agung Susanto (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
This article discusses the phenomenon of electric vehicles which are an alternative to reducing carbon emissions. This study discusses the intervention between the implementation of electric vehicles with interrelated dependent variables, one of which is nickel as raw material for battery emulsion. The phenomenon that occurs is that on the one hand electric vehicles can be used as an alternative to reducing carbon emissions, and on the other hand it hurts a negative impact on the environment related to nickel mining. In this case, ambivalence occurs between the text and the context in the field. Weak regulations make ambivalent phenomena ineffective in terms of application, especially to the environmental effects caused, so the author will focus on describing the ambivalence of the presence of electric vehicles in Indonesia, because, on the one hand, the presence of electric vehicles can reduce carbon emissions but on the other hand it can actually reduce carbon emissions. cause environmental damage. Therefore, to answer the above problems, the research method in this paper will use normative research methods with a focus on discussing and analyzing problem formulations related to how government policies regulate the use of renewable energy, especially regarding electric vehicles and their impact on environmental damage in Indonesia.